ISLAMIC MODERATION IN THE GOLDEN AGE OF ISLAM - Ahmad Choirul Rofiq (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2022)
There was a harmonious relation between Muslims and non-Muslims in the era of classical Islam, especially in the Abbasid dynasty. The Abbasids achieved the golden age of Islamic civilization because of their religious tolerance. Many non-Muslim scholars contributed their valuable works to intellectual achievement during the Abbasid reign. This paper expects to give an inspirative viewpoint on the relationship between Muslim and non-Muslim communities. Indonesia and its plural characteristic should build a harmonious multicultural relationship to imitate Abbasid achievements. Indonesia with its Muslim majority must prove that Islam is moderate and tolerant. Indonesian government together with all Islamic organizations and their followers should promote tolerant Islamic teachings, such as through multicultural Islamic education.